Online Shop Minniers’ Business Model Development Strategy Using the BCG Matrix Approach - Aulia, G M; Wahdiniwaty, R (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The development of the business world in the current era is developing in almost every country in the world, including the ASEAN region and Indonesia. This shift in business trends has made business competition in Indonesia even tighter, both online and offline sales. This business trend has an impact on the Korean and Thai Fashion businesses. The purpose of this research is to identify Minniers’ weaknesses, strengths, threats and opportunities and to recommend appropriate strategies to assist Minniers in developing their business and products. To collect data using primary data and secondary data, the author uses interview techniques with Minniers owners who then use SWOT analysis. While the secondary data collection technique is carried out through various sources such as books and articles, then internal and external factors are weighted. Data is processed using IFE and EFE. The next step is to determine the TOWS Matrix. and the final stage uses the BCG Matrix. The results of this study indicate Minniers are in quadrant I on the IE Matrix and quadrant II on the BCG Matrix. And by using Swot analysis and BCG Matrix, you can find out the current position of the company. This research shows that with proper analysis a company can find solutions in developing its business.